Peripheral Eosinophilia in Patients With Inflammatory Bowel Disease Defines an Aggressive Disease Phenotype. (December 2017) - Click, Benjamin; Anderson, Alyce M; Koutroubakis, Ioannis E; Rivers, Claudia Ramos; Babichenko, Dmitriy; Machicado, Jorge D; Hartman, Douglas J; Hashash, Jana G; Dunn, Michael A; Schwartz, Marc; Swoger, Jason; Barrie, Arthur; et al.
Abstract : OBJECTIVES: Peripheral blood eosinophilia (PBE) in inflammatory bowel disease (IBD) is associated with ulcerative colitis (UC) and active disease. Little data exist on the long‐term impact of PBE on disease course. We aimed to investigate the multi‐year patterns of PBE and its impact on disease severity in a large IBD cohort. METHODS: We performed a registry analysis of a consented, prospective, natural history IBD cohort at a tertiary center from 2009 to 2014. Demographics, comorbidities, disease activity, healthcare utilization, and time to hospitalization or surgical resection of patients who displayed PBE were compared to patients without PBE. RESULTS: Of the 2, 066 IBD patients, 19.2% developed PBE. PBE was significantly associated with UC ( P <0.001), extensive colitis ( P <0.001), and shorter disease duration ( P =0.03). Over six years, PBE patients had more active disease (Harvey–Bradshaw Index P =0.001; ulcerative colitis activity index P <0.001), concurrent C‐reactive protein elevation ( P <0.001), healthcare utilization (hospitalization P <0.001, IBD surgery P <0.001), and more aggressive medical therapy (prednisone P <0.001, anti‐TNF P <0.001). Patients with PBE had a significantly reduced time to hospitalization in both UC ( P <0.001) and Crohn's disease (CD) ( P <0.001) and reduced time to colectomy in UC ( P =0.003). On multivariable modeling, PBE remained significantly associated with hospitalization and surgery in both CD and UC. New diagnosis of UC with PBE was associated with increased steroid ( P =0.007) and anti‐TNF ( P =0.001) requirement. CONCLUSION: This multi‐year study of a large IBD cohort suggests that peripheral blood eosinophilia represents a biomarker of a distinct IBD subgroup, with a unique inflammatory signature, and at risk for worse clinical outcomes.